Pembelajaran Sosial-Emosional di Sekolah: Studi tentang Pembentukan Iklim Belajar - Ahmad Syarif Hidayat; Siti Maimunah Safitri; Muhammad Iqbal Fauzan (PT. Panca Publishing Indonesia, 2026)
Social-emotional learning (SEL) is widely recognized as an essential component of quality education, yet its contribution to classroom climate in Indonesian schools remains underexplored. This study examines how SEL practices shape learning climates across school levels in Bandar Lampung. A qualitative multiple case study involved sixteen participants, including teachers, students, and school counselors from four schools. Data were collected through in-depth interviews, focus group discussions, classroom observations, and document analysis, then analyzed using cross-case thematic analysis with triangulation and member checking to ensure credibility. Findings reveal four interconnected aspects: program integration, teacher support for emotional safety, peer interaction patterns, and resulting classroom climate characteristics. Consistent SEL practices were found to promote inclusive, psychologically safe, and academically supportive environments. Schools with stronger institutional commitment demonstrated more positive climate conditions. The study concludes that institutionalizing SEL requires sustained policy support, continuous teacher development, and a clear shift toward student-centered pedagogy.